Enhancing Students’ Communication Skills through Project Based Learning in Chemistry Instruction at MAN 2 Bengkalis - Aprilia Susilo, Resti; Amelia, Fitri; Yerimadesi, Yerimadesi; Noliea (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aimed to enhance students’ communication skills in chemistry through the application of Project Based Learning (PjBL) at MAN 2 Bengkalis. The study utilized a Classroom Action Research (CAR) design following the Kemmis and McTaggart framework, which includes the stages of planning, acting, observing, and reflecting across three cycles. The participants were 24 eleventh-grade students in the 2024/2025 academic year. Data were gathered using observation sheets to evaluate communication abilities and post-tests to measure learning achievement. The findings demonstrated a steady increase in students’ communication performance, improving from 73% in Cycle I to 81% in Cycle II and reaching 86% in Cycle III. Progress was evident in four key areas: accuracy of responses, participation in group discussions, presentation quality, and teamwork. Additionally, students’ learning outcomes showed notable gains, with mastery levels increasing from 54% in the first cycle to 88% in the final cycle. These results suggest that implementing PjBL effectively fosters active engagement, improves collaboration, and strengthens students’ conceptual understanding of chemistry concepts. In general, the use of this model contributes to a more dynamic and meaningful classroom experience, supporting the cultivation of essential 21st-century competencies.